Implementasi Kebijakan Pemerintah dalam Pengawasan Pangan Olahan Setelah Beredar di Indonesia - Nuriflalail Rio Jusepa; Mohammad Mulyadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
One of the functions of BPOM (the National Agency of Drug and Food Control) is to supervise processed food products after they are distributed. The objective of this study is to describe the implementation of Government Policies (BPOM) in Supervising Processed Food Products After They Are Distributed in Indonesia. According to BPOM’s 2022 Annual Report, routine inspections were conducted on 11,410 food distribution facilities, resulting in 8,221 (72.05%) facilities meeting the requirements (MK) and 3,140 (27.52%) facilities not meeting the requirements (TMK) in terms of applying Good Distribution Practices for Processed Foods (CPerPOB). The type of research used by the researcher is descriptive qualitative research, which studies existing issues and the established procedures. Based on the research findings, it shows that the implementation of BPOM policies has been conducted well, although there are some challenges. These challenges include the lack of available training or seminars for food inspectors, inadequate facilities and infrastructure, and the lack of networking across sectors.The solution provided by BPOM is to organize seminars or similar training sessions to align the understanding and perspectives between BPOM and business operators. The recommendation given in this study is to strengthen coordination between BPOM and business operators. This research can provide important information to the public,encouraging consumers to remain vigilant by frequently checking KLIK (Packaging, Label, Distribution Permit, and Expiry Date.